2021
DOI: 10.3389/fimmu.2021.607692
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Targeting the Transferrin Receptor 1 (TfR1) as Direct Anti-cancer Agents

Abstract: The transferrin receptor 1 (TfR1), also known as cluster of differentiation 71 (CD71), is a type II transmembrane glycoprotein that binds transferrin (Tf) and performs a critical role in cellular iron uptake through the interaction with iron-bound Tf. Iron is required for multiple cellular processes and is essential for DNA synthesis and, thus, cellular proliferation. Due to its central role in cancer cell pathology, malignant cells often overexpress TfR1 and this increased expression can be associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 171 publications
(294 reference statements)
1
101
0
2
Order By: Relevance
“…TfR1 has been explored as a potential therapeutic target due to its cell surface accessibility, constitutive endocytosis into cells, requirement for cell growth, and overexpression by cancer cells [ 13 ]. Among the developed therapeutic treatments targeting TfR1, antibodies stand out because of their exquisite specificity and high affinity [ 14 , 15 , 44 ]. TfR1 monoclonal antibodies, including 42/6, A24, JST-TFR09, and ch128.1Av (anti-hTfR1 IgG3-Av), facilitate the accumulation of nonselective therapeutic agents in cancer cells, elevate the intracellular drug concentration, improve anticancer activity, and enhance therapeutic efficacy [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…TfR1 has been explored as a potential therapeutic target due to its cell surface accessibility, constitutive endocytosis into cells, requirement for cell growth, and overexpression by cancer cells [ 13 ]. Among the developed therapeutic treatments targeting TfR1, antibodies stand out because of their exquisite specificity and high affinity [ 14 , 15 , 44 ]. TfR1 monoclonal antibodies, including 42/6, A24, JST-TFR09, and ch128.1Av (anti-hTfR1 IgG3-Av), facilitate the accumulation of nonselective therapeutic agents in cancer cells, elevate the intracellular drug concentration, improve anticancer activity, and enhance therapeutic efficacy [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…TfR1 is a candidate marker of poor prognosis in breast cancer ( Habashy et al, 2010 ). Therefore, TfR1 is a promising target in treating the cancers with overexpressed TfR1 and increased iron demands ( Candelaria et al, 2021 ). Anti-TfR1 antibodies have been demonstrated to be an efficient therapy for leukemias and lymphomas ( Neiveyans et al, 2019 ).…”
Section: Iron and Cancermentioning
confidence: 99%
“…It has been shown that TfRs are overexpressed, 2–10-fold, in most tumor cells, including breast, lung, brain, liver, ovarian prostate and colon cancer cells, and are directly involved in the process of iron homeostasis and cell proliferation, making them attractive and effective targets for site-specific antitumor drug delivery [ 41 ]. TfRs are therefore interesting targets in the development of ligand-based nanotherapies that involve the natural ligand Tf, mAbs or single-chain variable fragments (scFv) [ 42 , 43 ]. The Tf approach has been most thoroughly investigated for drug delivery to the brain, as the Tf ligand facilitates transcytosis of the conjugated drug-carrier systems across the blood brain barrier (BBB).…”
Section: Ligands For Active Targeting and Receptor-based Active Targeting Strategiesmentioning
confidence: 99%